The Influence of Obesity on Blood Pressure in Early Adulthood and Middle Adulthood Males - Muhammad O A Eusman; Hana Ratnawati; Mariska Elisabeth (Journal of Medicine and Health, 2019)
Hypertension is commonly found in obesity patients. Age affects the occurrence of hypertension. The aim of this study is to determine the effect of obesity on blood pressure levels in early adulthood males (<35 years) and middle adulthood males (?35 years). This is an observational analytic study using data from medical check-up records of male adult office workers in Bandung. The data was analyzed with Mann-Whitney test (? = 0.05) and Chi-Square to find the odds ratio (OR). The results showed that out of 110 data in medical records, there were 79 (71.82%) obese and 31 (28.18%) non-obese. In early adulthood males (<35 years) there is no significant difference between non-obese with obese in systolic blood pressure (p=0.779) and diastolic blood pressure (p=0.779). In middle adulthood males (?35 years) there was a highly significant difference between non-obese with obese on systolic blood pressure (p=0.001) and diastolic blood pressure (p=0.003). There was a significant relationship between obesity and hypertension (p=0.048) with OR=3.73. In conclusion, in early adulthood males (<35 years) obese does not have an effect on the development of hypertension, while in middle adulthood males, obesity increases the risk of developing hypertension by 3.73 times. Keywords: obesity, blood pressure, early adulthood males, middle adulthood males